When Long-Lasting Food Selectivity Leads to an Unusual Genetic Diagnosis: A Case Report. - Da Lozzo, Prisca; Magnolato, Andrea; Del Rizzo, Irene; Sirchia, Fabio; Bruno, Irene; Barbi, Egidio (J Adolesc Health, 2019)
Hereditary fructose intolerance is an autosomal recessive disorder of fructose metabolism caused by catalytic deficiency of aldolase B enzyme [1]. The disease is typically expressed when fructose- and sucrose-containing foods are first introduced in the diet; acute manifestations include nausea, vomiting, abdominal distress, and symptomatic hypoglycemia [1,2]. Chronic fructose ingestion eventually leads to poor feeding, growth retardation and gradual liver and/or renal failure [3,4]. Some patients may remain undiagnosed until adulthood because of a self-protective avoidance of sweet tasting food that prevents the development of acute toxicity from fructose containing food; however, these subjects may suffer intermittent symptoms throughout life, leading to potentially serious misdiagnosis [4]. We report the case of a patient with unrecognized hereditary fructose intolerance in which chronic gastrointestinal complaints, low body weight, and unexplained food avoidance were addressed as manifestations of an eating disorder during adolescence.